Denial : why business leaders fail to look facts in the face--and what to do about it - Tedlow, Richard S. (New York : Portfolio, 2010)
The Harvard Business School professor and author reveals the sources and consequences of denial in business, citing numerous examples from top organizations while identifying leadership skills for recognizing and countering harmful denial behaviors.
Shooting the messenger: Henry Ford and the Model T -- What denial is, and is not -- The technological chasm: denial in the tire industry --'They just didn't believe these things were happening': Denial at the A&P -- The edifice complex: Denial at Sears -- Success today vs. success tomorrow: Denial and the IBM PC -- Coke's new formula for denial -- The madness of crowds: Delivering denial at Webvan -- Strategy, structure, and facing facts at DuPont --'Why shouldn't you and I walk out the door...?': A new perspective at Intel -- Data-driven emotional intelligence: Tylenol's comeback -- A new point of view.
Includes bibliographical references (p. [241]-252) and index.
Keywords: Management -- Psychological aspects; Denial (Psychology); Business failures -- Case studies